Effect of deceptively aggressive bike pacing on sprint-distance triathlon performance - Taylor, D.; Smith, M. F. (Journal of Science and Cycling, 2015)
Introduction: Whilst aggressive bike pacing has been found to impair subsequent run performance during triathlon, this strategy appears to enhance total cycle-run time over the sprint-distance format (Suriano & Bishop, 2010). As such, cycling at the highest sustainable intensity (i.e. isolated TT power output) is suggested as the best strategy to optimise overall performance time in the event. However, it is unclear how an athlete`s expectations, beliefs and perceptions influence the effectiveness of such pacing during multi-modal events, such as triathlon. Taylor & Smith (2013) have suggested that practically meaningful changes in triathlon running may result from deceptive pace manipulation, equivalent to the smallest worthwhile change in performance. With this in mind, deceptively aggressive bike pacing may enable triathletes to maximise their sustainable intensity in this discipline, without the impairments in run performance typically associated with this strategy. However, this is yet to be confirmed by experimental evidence. This study therefore examined the effects of deceptively aggressive bike pacing on sprint- distance triathlon performance.